2015
DOI: 10.1038/npp.2015.305
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline-Induced Elevation of Dopamine in Smokers: A Preliminary [11C]-(+)-PHNO PET Study

Abstract: Varenicline, a nicotinic partial agonist, is the most effective treatment for tobacco use disorder. However, its mechanism of action is still unclear and may involve stimulating dopaminergic transmission. Here we used PET imaging with [11 C]-(+)-PHNO to explore for the first time the impact of varenicline on dopamine transmission in the D2-rich striatum and D3-rich extra-striatal regions and its relationship with craving, withdrawal and smoking. Eleven treatment-seeking smokers underwent two PET scans with [11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…In this study, the lack of differences between the baseline scan and the scan performed after at least 3 weeks of wash‐out suggest that the changes in BP ND are not permanent and associated with the exposure to prazosin. It should be noted that the magnitude of increase found in the present study is consistent with the degree of decrease found in other studies using either [ 11 C]‐(+)‐PHNO (Di Ciano et al, ) or [ 11 C]‐raclopride (Martinez et al, ), suggesting that the changes observed in the present study were biologically relevant. In this regard, the basal level of BP ND observed in the DC, although small, is consistent with previous reports from a number of groups using [ 11 C]‐(+)‐PHNO (Di Ciano et al, ; Erritzoe et al, ; Matuskey et al, ; Matuskey et al, ; Matuskey et al, ; Searle et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the lack of differences between the baseline scan and the scan performed after at least 3 weeks of wash‐out suggest that the changes in BP ND are not permanent and associated with the exposure to prazosin. It should be noted that the magnitude of increase found in the present study is consistent with the degree of decrease found in other studies using either [ 11 C]‐(+)‐PHNO (Di Ciano et al, ) or [ 11 C]‐raclopride (Martinez et al, ), suggesting that the changes observed in the present study were biologically relevant. In this regard, the basal level of BP ND observed in the DC, although small, is consistent with previous reports from a number of groups using [ 11 C]‐(+)‐PHNO (Di Ciano et al, ; Erritzoe et al, ; Matuskey et al, ; Matuskey et al, ; Matuskey et al, ; Searle et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…Given that dysfunction within dopaminergic systems is implicated in the pathophysiology of ADHD (Volkow et al, 2009), varenicline’s impact on striatal dopamine transmission (Di Ciano et al, 2016; Feduccia et al, 2014) may serve to reduce the severity of ADHD symptoms via facilitation of dopamine transmission within brain regions associated with reward and motivation, such as the striatum. These molecular actions may also explain varenicline’s efficacy in reducing withdrawal, given that nicotine withdrawal is associated with reductions in basal dopamine levels in the striatum (Zhang et al, 2012).…”
Section: 0 Discussionmentioning
confidence: 99%
“…Exercise was proposed as a smoking-cessation aid long ago, and there are some reports of benefits from exercise in reducing tobacco consumption, albeit with limited evidence of long-term benefit (Ussher et al, 2014). In addition, subchronic administration of varenicline, which has efficacy in promoting smoking cessation, produces striatal D2/3 receptor upregulation in rats (Crunelle et al, 2009) as well as dopamine release in striatum, demonstrated by [ 11 C]-(+)-PHNO and PET in smokers (Di Ciano et al, 2015). …”
Section: Discussionmentioning
confidence: 99%